Effectiveness from the perspective of project management in the local government units in Poland − empirical research results - Dolata, Magdalena (Management Sciences, 2014)
In the research carried out by one of Polish research agencies [Pentor 2010], local administration offices were in general seen as institutions which, despite high expenditures, maintained inefficient operations and as a result did fully satisfy the needs of citizens. In addition, searching for the causes of failures in projects, the lack of professional approach to project management should be highlighted, which relates to the undertaken ad hoc adaptation activities to changes in the environment, and the implementation of projects in interim and in unsystematic way. The research found that the consequence of this state of affairs was the reduction of the effectiveness of implementation of projects and of synergistic effect created by audited entity. As a result, the growing importance of project management in the functioning of local government units in Poland, with low levels of performance previously practiced in this field, tended to take the search for a new approach to project management in the units
Nauki o Zarządzaniu = Management Sciences, 2014, Nr 4 (21), s. 36-49
Keywords: project management; basic units of local government; effectiveness of project management; zarządzanie projektami; podstawowe jednostki samorządu terytorialnego; skuteczność zarządzania projektami